Effect of ginger water therapy on reducing menstrual pain in female nursing students: An experimental study - Pambudi, Amrih Prasetyo Tri; Adiutama , Novian Mahayu; Fauziah, Wardah (Indonesian Nursing Journal, 2023)
Background: Women often complain of painful periods before or during menstruation. Plants that are believed to relieve pain include ginger (Zingiber Officinale Rose), whose rhizomes have analgesic, antipyretic, and anti-inflammatory properties. Purpose: To determine the effect of ginger water therapy on reducing menstrual pain in nursing students. Methods: This research was conducted on nursing students at Politeknik Negeri Subang using a quasi-experimental research design with a pre-post-test design with control group. The stratified random sampling was used with the number of respondents at 30 divided into two groups: a 15-person intervention group and a 15-person control group. Data were collected using the Numeric Rating Scale (NRS) pain scale. Results: The study found that the mean pre-treatment menstruation pain scale was 5.27 for the intervention group and 4.73 for the control group, and the mean post-treatment menstruation pain scale was 1.93 for the intervention group and 4.00 for the control group. Data analysis obtained a p-value of <0.001 (0.05), indicating that there was an effect of ginger water therapy on reducing the menstrual pain scale. Conclusion: These findings have verified the initial possibility of ginger's efficacy in reducing menstrual pain, although it should be given to women with mild-moderate menstrual pain. We strongly recommend further research with larger numbers of patients on the efficacy and protection of different doses of ginger.